Implementasi Service Oriented Architecture (SOA) pada Sistem Pencatatan Keuangan untuk UMKM: Implementation of Service Oriented Architecture (SOA) in the Financial Recording System for UMKM - Royana Afwani; Muhammad Iksanul; Moh. Ali Albar (Journal of Computer Science and Informatics Engineering (J-Cosine), 2022)
One of the indications of a UMKM's success is financial statements. UMKM can use SAK EMKM to prepare financial reports. Many UMKM, on the other hand, have yet to incorporate SAK EMKM. UMKM can use information technology to improve its financial records. With the quantity and scope of UMKM, as well as the demand for information technology, flexible systems must be established on a variety of platforms in order to be sustainable. As a result, SOA must be used in the financial recording system for UMKM. As a result of these issues, a SOA-based Financial Recording System was developed. SOA allows the system to be more adaptable and reusable. The system built consists of a service provider and a cloud consumer. Owners of UMKM can use the Android application to keep financial records and generate reports from service providers. According to the results of the Black Box approach, every service offered at the service provider, as well as the cloud consumer's function, has been performing as predicted. And, according to the proprietor of UMKM, the system has been performing admirably.